Morphology and typology of Islamic dome architectural design in the middle east and central Asia: persian islamic dome - Azzahrah, Sharifah Fatimah; Salih, Sarah Abdulkareem; Sabil, Azmal; Asif, Nayeem; Ismail, Sumarni (Human Resources Management Academic Research Society (HRMARS), 2023)
Dome has been a significant element and structure in the architecture of Islam, where it usually can be found in mosques from many years ago, which started from the Umayyad period in Jerusalem (691 AD). However, the persistent practice of domes in modern Islamic architecture led to the development and evolution of dome concepts and types. Therefore, the current paper aims to analyze and classify the dome architectural design and how it evolved in Central Asia and the Middle East over time. The current paper used a systematic search and narrative review of 26 publications published in English in Scopus and ScienceDirect databases before 2023. The current study reviewed the Islamic dome's morphology in six different periods that emerged in Central Asia and the Middle Eastern: the pre-Islam, early Islam, Seljuk era, Ikhanids and Timurids era, Safavids and Qajar era, and Contemporary period. Further, it highlighted three main stylistic classifications of Islamic domes: dome shape, type of shell, and type of support. The current review study contributed to a deeper understanding of the Islamic dome's morphology and stylistic classifications through time.